PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING MENGGUNAKAN MEDIA EDUCAPLAY PADA MURID KELAS IV SEKOLAH DASAR - Putri Zudhah Ferryka; Faizatul Ma’rifah; Dwi Ayu Lestari; Dyah Ayu Ihza Yunita; Dyah Isna Nurhayati; Erlina Setyowati; Hanania Ayu Widya; Indra Siswanti (STKIP Subang, 2026)
This study was motivated by the low mathematics learning outcomes of fourth-grade students at SDN 2 Karangan on data presentation material, particularly pictograms and bar charts. Based on the initial evaluation results, only 4 out of 13 students (31%) achieved learning mastery. This problem was caused by teacher-centered learning, the lack of innovative learning models, and the limited use of interactive learning media. This study aimed to improve students’ mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by Educaplay media for fourth-grade elementary school students. This research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects of this study were 13 fourth-grade students of SDN 2 Karangan in the 2025/2026 academic year. Data were collected through tests, observations, and documentation. The data were analyzed quantitatively and qualitatively by calculating the average learning outcomes and the percentage of classical mastery learning. The results showed a significant improvement in students’ mathematics learning outcomes across cycles. In Cycle I, the average score was 65.38 with a classical mastery percentage of 46%. After improvements were made in Cycle II through the implementation of more interactive Educaplay media and more optimal problem-based learning activities, the average score increased to 87.69 with 100% classical mastery. The implementation of the Problem Based Learning model assisted by Educaplay media proved effective in improving the mathematics learning outcomes of fourth-grade students at SDN 2 Karangan on data presentation material.